KADAR AIR, pH, SUHU, DAN KADAR AMONIA PADA LITTER DI DUA ZONASI YANG BERBEDA PADA KANDANG CLOSED HOUSE - Cakra Rakasiwi Mega Jaya; RR Riyanti; Dian Septinova; Khaira Nova (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2022)
This research was a case study which aimed to determine the water content, ammonia content, pH, and temperature of litter in the zonation in the closed house. This research was carried out in March 2021-April 2021, for 28 days in the Closed-house unit of the Department of Animal Husbandry, Faculty of Agriculture, University of Lampung. The closed house unit used was 40 meters long and 8 meters wide with a capacity of 5,495 broiler DOCs. The closed house zone was divided into two, namely zone 1 (20x8m) located near the cooling pad occupied by 2,747 DOCs and in zone 2 (20x8m) which is near the exhaust fan occupied by 2,748 DOCs. The results showed that Zone 1 near the cooling pad had lower water content, ammonia, pH, and litter temperature compared to Zone 2 which was close to the exhaust fan. Keywords: Ammonia, Closed-house zoning, Litter temperature, pH, Water content